LITERATUR REVIEW : PERILAKU KONSUMEN DALAM PLATFORM E-COMMERCE DI ERA DIGITAL (A LITERATURE REVIEW: CONSUMER BEHAVIOR ON THE PLATFORM E-COMMERCE IN THE DIGITAL ERA) - Nduru, Melanie Putri; Sitanggang, Herikson Muksa Putra; Panggabean, Susi; Matondang, Khairani Alawiyah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to understand consumer behavior on e-commerce platforms in the digital era through a literature review approach. The method used is a review of studies published between 2019 and 2024. The study focuses on factors that influence purchasing decisions, such as easy access, trust in platforms, promotions, customer reviews, and lifestyle. The results show that the convenience of shopping, a wide range of products, personalized features, and online marketing strategies are the main reasons consumers prefer e-commerce over physical stores. Additionally, cultural factors, technology trends, and growing trust in online payment systems also support the rise of online shopping habits. These findings provide useful insights for businesses to create better marketing strategies, improve customer satisfaction, and stay competitive in the digital marketplace.